A New Species of Hemicotelles (Hymenoptera: Colletidae) from Peru - Apaza, L. Vanessa Anaya; Maldonado, Javier Huanca; Packer, Laurence (Zootaxa, 2024)
We diagnose, describe and illustrate Hemicotelles misti Anaya, Huanca and Packer n. sp., from the slopes of the Misti Volcano in Arequipa Province, Peru. The new species represents a range extension of 1500 km from the nearest confirmed locality for the genus, in Central Chile. We provide a fully illustrated key for the identification of the three species in the genus and add the species to an earlier phylogeny for Colletinae.